Sleep in the City. Private Experience of Beauty and Its Urban Implications - Pokorski, Bartosz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
In my paper I try to trace and understand the reasons for the birth of the 24/7 world as it is described by Johnatan Crary in his book 24/7 Late Capitalism and the Ends of Sleep. He proposes a grim vision of late capitalism in which sleep deprivation and the disintegration of public and private spaces will become a market necessity. My attempt to understand is supported on two other authors. First, Hannah Arendt provided me with an analysis of origins, transformations and somewhat present version of the relation of private and public spheres. Second, Fredrich Schiller delivered an interesting theory on the aesthetic ideal, art, beauty and human experience of beauty. These three analyzes stand as basis for my attempt to present a proposal to overcome the crisis described by Crary and the answer is related to the issue of aesthetic experience of street art in urban space.